Effect of Solo Garlic Extract (Allium Sativum) on Malondialdehyde (MDA) in Rats (Rattus Norvegicus) Exposed to Cigarette Smoke - Kinasih, Dewangga Sakti Satria; Meliana, Ahila; Safitri, Indri (poltekkes kemenkes mataram, 2024)
Cigarette smoke is one of the oxidant sources which cause stress oxidative. Cigarettes contain more than 4500 gases and chemicals that have negative effect on human body. Stress oxidative is marked by various parameters, one of which is malondialdehyde (MDA). As natural plant, solo garlic has a potential as antioxidant because contain a lot of active compounds. This study determines the effect of solo garlic on MDA level of Rattus norvagicus which exposed to cigarette smoke. This study is experimental animal study which use randomized posttest only control group design. Twenty-five rats were included and divided into five groups, such as negative control, positive control, and the treatment groups. Solo garlic administrated at doses of doses of 2.5, 5, and 10 (mg/200gBW/day) respectively. The statistical result showed that solo garlic extract can reduce the MDA level of treatment groups (p=0.000). This study concluded that solo garlic extract can reduce the MDA levels of rats to cigarette smoke. The significant effect was obtained at a dose of 10 mg/200gBW/day.